Correction: Effect of dye end groups in non-fullerene fluorene- and carbazole-based small molecule acceptors on photovoltaic performance. Issue 92 (8th October 2015) - Kim, Yujeong; Song, Chang Eun; Moon, Sang-Jin; Lim, Eunhee
<x xml:space="preserve">Abstract</x> Correction for 'Effect of dye end groups in non-fullerene fluorene- and carbazole-based small molecule acceptors on photovoltaic performance' by Yujeong Kim et al., RSC Adv., 2015, 5, 62739–62746.